APPLIED INFORMATION SYSTEMS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The article discusses practical information systems, their structure and main goals, areas of application. The principle of operation of the initial, mechanized, automated, automated types of information systems is disclosed.